Pengaruh ukuran perusahaan,profitabilitas perusahaan, laba rugi perusahaan, reputasi kantor akuntan publik (kap) dan opini auditor terhadap audit delay pada perusahaan yang terdaftar di bei tahun 2011-2012 - Illa Sasmi Herja; Muhammad Rasuli; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to examine the effect of firm size, firm profitability, profit/loss, reputation of a public, auditor’s opinion to audit delay in Indonesia Stock Exchange.The sampling method used was purposive sampling and obtained sample 341 companies. The study period is 2011 until 2012. To analyze the data in this study used multiple regression test (multiple regression).Result of analyze showed that independent variabels affect dependen variable on 54,4%.And from the test results it can be concluded that firm size significantly. firm profitablity significantly, profit/loss significantly, reputation of a public accounting firm significantly and auditor’s opinion significantly influence audit delay during the period of this study.Keywords: Audit delay, firm size, firm profitability, profit/loss, reputation of a public accounting firm, auditor’s opinion.